2007
DOI: 10.1007/s11661-007-9271-x
|View full text |Cite
|
Sign up to set email alerts
|

Shear Localization: A Historical Overview

Abstract: This review presents a historical approach to the development of understanding of the shear localization phenomenon in materials, concentrating particularly on impact. Deformation localization under these conditions is widely referred to as adiabatic shear banding as the timescales are such that the distances heat can diffuse are small. Dimensional analysis shows that the phenomenon is ultimately intractable to linear algebraic analysis, as it is a coupled mechanical/thermal problem. However, various linear an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
56
0
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(61 citation statements)
references
References 139 publications
(153 reference statements)
3
56
0
2
Order By: Relevance
“…The theories by Grady and Kipp, [86] Wright and Ockendon, [88] and Molinari [89] are presented in the companion paper in these proceedings by Walley. [224] The three equations are given in Table III. We describe briefly below the evolution of multiple adiabatic shear bands in commercially pure titanium and Ti-6Al-4V alloy through the radial collapse technique of a thick-walled cylinder under highstrain-rate deformation (experimental configuration [219] with results by Xue et al [39] shown in Figure 1(c).…”
Section: Spacing and Self-organization Of Shear Bandsmentioning
confidence: 99%
“…The theories by Grady and Kipp, [86] Wright and Ockendon, [88] and Molinari [89] are presented in the companion paper in these proceedings by Walley. [224] The three equations are given in Table III. We describe briefly below the evolution of multiple adiabatic shear bands in commercially pure titanium and Ti-6Al-4V alloy through the radial collapse technique of a thick-walled cylinder under highstrain-rate deformation (experimental configuration [219] with results by Xue et al [39] shown in Figure 1(c).…”
Section: Spacing and Self-organization Of Shear Bandsmentioning
confidence: 99%
“…(4) is the same as the momentum equation of Burns and Davies (2002). Compared with the momentum equation in simple shear (Dodd and Bai, 2012;Meyers, 1994;Walley, 2007;Wright, 2002), the effect of the compressive stresses from the tool and the constraint as well as material convection due to chips flow are added in Eq. (4) during DLSEM.…”
Section: Theoretical Modeling For Dlsemmentioning
confidence: 99%
“…Transformed bands in steels may be as narrow as 5-10 μm and will appear white after nital etching. Deformed bands in steels are generally broad and do not etch white [10,11].…”
Section: Introductionmentioning
confidence: 99%